Analys av kostnadsvariationer i en prototyprealiseringsprocess i bilindustrin - Bengtsson, Hanna; Nilsson, Desiree (My University, 2018)
This project was conducted at a relatively new enterprise in the automotive industry. The goal was to find the reason for cost variations when building boxcars. This was a process analysing project conducted using the Lean Six Sigma methodology. First thing was to map the process, since the current boxcar process was undefined and therefore unclear, even for the employees. The boxcar process has many process steps, involving handovers to different functions, a long lead time and much manual labour. Many boxcar parts are subject to deviation during the process and needs to be re-ordered, which causes time delay and excessive costs. When working with this project, it was early discovered that important basic statistics that should be easy to find, was not. Today it is hard to keep track of where the money goes since several Purchase Requisitions (PR’s) are used for the same boxcar and sometimes the same PR is used for different boxcars. To be able to keep track of the cost for each boxcar, a suggested action is to only make one PR for each boxcar status. The costs should be tracked and visualized in, for example, a control chart. The quality of the collected data for this project affects the validity of the results. Available statistics for example boxcar costs, reasons for deviations and number of deviations has a low precision. This report relies on a correlation between number of deviations and total cost and between lead time and total cost when building boxcars. This statement has not been proved, but should be further investigated. Working with the project, it became clear that one of the departments that supply input for the process, are not aware of their importance and involvement in the boxcar process. This means that working with the boxcar process is extra work for the engineers at this department. Therefor another suggestion of improvement is to start a discussion whether it should be a part of the engineers’ job description.
Keywords: Produktion; Maskinteknik; Materialteknik; Production; Mechanical Engineering; Materials Engineering